Разработка структуры генератора случайных изменений напряжений в электрических сетях промышленных предприятий - Кузнецов, Виталий Вадимович; Николенко, Анатолий Васильевич; Иващенко, Валерий Петрович (НТУ "ХПИ", 2013)
The stochastic generator of casual changes of tensions is worked out in the electric systems of industrial enterprises, allowing to decide the different tasks of energy’s efficiency of asynchronous engines with a shortcircuited rotor at presence of deviations of quality’s indexes of electric power from rationed.
Keywords: показатели качества электроэнергии; системы электроснабжения; стохастический генератор; энергоэффективность асинхронных двигателей; короткозамкнутый ротор